2011
DOI: 10.1111/j.1744-6155.2010.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of nonpharmacological methods for children's postoperative pain relief: Singapore nurses' perspectives

Abstract: Nurses need training and education on nonpharmacological pain relief methods, particularly on methods that have been shown to be effective in prior research but that were less often used by nurses in this study: massage, thermal regulation, imagery, and positive reinforcement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
1
12
0
1
Order By: Relevance
“…Moreover, our results show, that encouraging children to ask about their misconceptions as well as making sure, that they understand the information, are also warrant for more attention to postoperative pain control. In this study, the half of nurses reported to give routinely preparatory information and the same finding has been revealed in the study from He et al [34].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Moreover, our results show, that encouraging children to ask about their misconceptions as well as making sure, that they understand the information, are also warrant for more attention to postoperative pain control. In this study, the half of nurses reported to give routinely preparatory information and the same finding has been revealed in the study from He et al [34].…”
Section: Discussionsupporting
confidence: 85%
“…According to these results, ıt is considered, that nurses in the study from He et al [34] pay more attention to inform patients postoperatively about these techniques. It can be concluded, that more attention should be paid to inform patients about other possible pain relieving techniques in these areas to optimize postoperative pain control.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, future studies should control the confounding effects of types of surgery and pain medication on children's perioperative anxiety, negative behaviors, and postoperative pain. In addition, because of the fact that nonpharmacologic methods were also reported to be used to help relieve children's postoperative pain (He et al, 2007(He et al, , 2011 Among the six studies, two (Fincher et al, 2012;Kain et al, 1998) examined the effectiveness of therapeutic play intervention in parents' anxiety. Both studies found significant, positive effects on parents' anxiety before operation, as confirmed by both subjective and objective outcome measurements (Fincher et al, 2012;Kain et al, 1998).…”
Section: Discussionmentioning
confidence: 99%